Defending Women Beyond Feminism: Gender Perspectives in Indonesia - Nur Mutiullah, Muhammad Yaufi (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2024)
This article examines the development of gender understanding in Indonesia. Specifically, the understanding of gender discussed in this article comes from the perspective of one of the leading Islamic organizations in Indonesia, namely Nahdlatul Ulama (NU), which has its own way of thinking in defending women's rights. This article aims to show that Nahdlatul Ulama's concept of defending women is different from the concept of feminism that emerged in Western civilization, namely by looking at the capabilities and capabilities of women themselves. Therefore, I use the words